Student's manual on the constitution - De Leon, Hector S. (Manila, Philippines : Rex Book Store, 2010)
This modest volume which is actually the sixth edition, attempts to explain very briefly and in simple and clear language the provisions of the basic charter, now a curricular subject in all schools. Although it is aimed primarily at students in educational institutions other than law schools, law students will find the work useful reference.
Introduction -- Preamble -- Article I- National Territory -- Article II- Declaration of principles and State Policies -- Article III- Bill of Rights -- Article IV- Citizenship -- Article V- Suggrage -- Article VI- Legislative Department -- Article VII- Executive Department -- Article VIII- Judicial Department -- Article IX- Constitutional Commissions -- Article X- Local Government -- Article XI- Accountability of Public Officers -- Article XII- National Economy and Patrimony -- Article XIII- Social Justice and Human Rights -- Article XIV- Education, Science and Technology, Arts, Culture, and Sports -- Article XV- The Family -- Article XVI- General Provisions -- Article XVII- Amendments of Revisions.
Keywords: CONSTITUTION -- PHILIPPINES